2020
DOI: 10.1111/cogs.12893
|View full text |Cite
|
Sign up to set email alerts
|

How Experts Adapt Their Gaze Behavior When Modeling a Task to Novices

Abstract: Domain experts regularly teach novice students how to perform a task. This often requires them to adjust their behavior to the less knowledgeable audience and, hence, to behave in a more didactic manner. Eye movement modeling examples (EMMEs) are a contemporary educational tool for displaying experts’ (natural or didactic) problem‐solving behavior as well as their eye movements to learners. While research on expert‐novice communication mainly focused on experts’ changes in explicit, verbal communication behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Results showed that experts watched the tools for a shorter time and the ball for a longer time than novices did [ 22 ]. The eye-tracking technology allowed the distinctions in visual perception of the experts and novices [ 23 , 24 , 25 , 26 ]. Typically, novice clinicians tend to unnecessarily activate data-collection approach to validate their hypothesis before arriving at a final diagnosis while experts make appropriate assumptions more quickly based on past similar experiences and accurately perceive more precisely the relative importance of information such as case progression, vital signs, and symptoms [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that experts watched the tools for a shorter time and the ball for a longer time than novices did [ 22 ]. The eye-tracking technology allowed the distinctions in visual perception of the experts and novices [ 23 , 24 , 25 , 26 ]. Typically, novice clinicians tend to unnecessarily activate data-collection approach to validate their hypothesis before arriving at a final diagnosis while experts make appropriate assumptions more quickly based on past similar experiences and accurately perceive more precisely the relative importance of information such as case progression, vital signs, and symptoms [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Visual attention was measured in terms of eye movement, including DT and FC. The reason why DT and FC were used is that they have shown potential in detecting cognitive processes during visual search, especially in problem-solving analysis [ 20 , 21 ]. In contrast to measuring mean tendency of visual attention, the LSA [ 22 ], LMMs, and TE were used to explore the distribution of attention on the AOIs, as well as temporal relationships among AOIs (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The didactic explanations can be adapted to the level of learners and make them more understandable for the learner (Isaacs & Clark, 1987). Additionally, the eye movements of experts became more similar to novices when behaving didactically (Emhardt et al, 2020). The authors argue that this behaviour may facilitate following the experts task solving behaviour for novices.…”
Section: Trainings To Improve Medical Image Processingmentioning
confidence: 97%